2014
DOI: 10.1016/j.ejmhg.2014.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Study of genotype–phenotype correlation of methylene tetrahydrofolate reductase (MTHFR) gene polymorphisms in a sample of Egyptian autistic children

Abstract: Background: Classical autism belongs to a group of heterogeneous neurobehavioral disorders known as autism spectrum disorders (ASDs) characterized by abnormalities in social interaction, impaired communication, and repetitive stereotypic behaviors. Overall, there is an increased risk of ASDs associated with common mutations affecting the folate/methylation cycle. This study aimed at identification of the C677T polymorphic genotypes of MTHFR gene among the Egyptian children with autism and to correlate them wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
8
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 32 publications
6
8
1
Order By: Relevance
“…57 El-Baz et al 44 reported that the heterozygotes 677C/T and 1298A/C were found equally (46.2%) in ASD cases with severe CARS scores, and no significant differences were found between severe and mild/moderate cases, according to CARS scores. However, in contrast to previous studies in Egyptian populations, 44,58 our study in the Saudi population showed a significant difference in the frequency of the 677C>T and 1298A>C SNPs when comparing CARS scores <37 and CARS scores ≥37 (P = 0.001, and P = 0.0014) in the non-additive models.…”
Section: Discussioncontrasting
confidence: 99%
“…57 El-Baz et al 44 reported that the heterozygotes 677C/T and 1298A/C were found equally (46.2%) in ASD cases with severe CARS scores, and no significant differences were found between severe and mild/moderate cases, according to CARS scores. However, in contrast to previous studies in Egyptian populations, 44,58 our study in the Saudi population showed a significant difference in the frequency of the 677C>T and 1298A>C SNPs when comparing CARS scores <37 and CARS scores ≥37 (P = 0.001, and P = 0.0014) in the non-additive models.…”
Section: Discussioncontrasting
confidence: 99%
“…This is in agreement with previous reports (20). C667T polymorphism genotyping was consistent with the study of Elif et al (19) that revealed the heterozygote 667CT as the most prevalent genotype among patients.…”
Section: Discussionsupporting
confidence: 94%
“…Rai et al [ 26 ] investigated 1978 cases and 7257 controls (Caucasians: 1355 cases and 6460 controls; Asians: 623 cases and 797 controls) in 13 studies [ 18 , 22 , 27 , 28 , 31 , 33 , 35 , 43 , 44 , 46 , 48 , 50 ] and found that C677T polymorphism of MTHFR is a risk factor for ASD susceptibility as well [ 26 ]. Similarly, the current meta-analysis enrolled 2609 cases and 7496 controls (Caucasian: 1786 cases and 6499 controls, Asian: 823 cases and 997 controls) from 15 selected literature [ 9 , 18 , 22 , 26 – 28 , 31 , 32 , 33 , 35 , 43 , 47 , 48 , 50 ], further confirmed the association between C677T polymorphism of MTHFR and ASD susceptibility.…”
Section: Discussionsupporting
confidence: 70%
“…In the present meta-analysis, eight of the selected articles [ 18 , 22 , 32 , 35 , 36 , 43 , 44 , 47 , 50 ] had enrolled 1961 cases and 1652 controls (Caucasians: 1387 cases and 991 controls, Asians: 574 cases and 661 controls), and it was recognized that A1298C polymorphism of MTHFR was not correlated with ASD susceptibility. However, Khalil et al (42 cases and 48 controls) [ 49 ] and El-Baz et al (31 cases and 39 controls) [ 32 ] revealed that MTHFR A1298C polymorphism represented a risk factor in association with ASD.…”
Section: Discussionmentioning
confidence: 99%